Soap bubbles for large-scale PIV in industrial wind tunnels - Engler Faleiros, D.; Tuinstra, Marthijn; van Rooijen, Bart D.; Scarano, F.; Sciacchitano, A. (Universität der Bundeswehr München, 2019)
This work evaluates the use of helium-filled soap bubbles (HFSB) for Particle Image Velocimetry (PIV) measurements at high Reynolds numbers (up to 3.2 million) in aeronautics. The measurements are performed in the Low Speed Tunnel (LST) of the German-Dutch Wind Tunnels (DNW) using a high-lift airfoil in close-to-stall conditions up to 70 m/s. Experiments using Di-ethylhexyl- sebacat (DEHS) particles are performed for a comparison of the two seeding techniques. The signal to noise ratio of HFSB images was two orders of magnitude larger than that of DEHS, which strongly reduced the unwanted effects of background reflections and light intensity spatial variations, compared to DEHS particle images. The mean velocity field obtained with HFSB exhibits differences typically within 1% of the free stream velocity, when compared to DEHS measurements.
Keywords: Windtunnels; Particle Image Velocimetry (PIV)